2021
DOI: 10.1001/jamainternmed.2020.6895
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia and Physician-Assisted Suicide in Patients With Multiple Geriatric Syndromes

Abstract: Key Points Question What are the patient characteristics and circumstances associated with the request for euthanasia and physician-assisted suicide (EAS) in cases of multiple geriatric syndromes as reported in the case summaries of the Dutch Regional Euthanasia Review Committees? Findings In this qualitative study of 53 case summaries published by the Dutch Regional Euthanasia Review Committees, a combination of multiple geriatric syndromes, such as visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…Moreover, the documents used are abbreviated representations of complex cases, made suitable for publication on an open access website and selected for predominantly educational purposes. They contain “plain language” with little medical, social and historical context‐descriptions 3,27 . Since much standardized wording was used, we coded non‐standard texts with special attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the documents used are abbreviated representations of complex cases, made suitable for publication on an open access website and selected for predominantly educational purposes. They contain “plain language” with little medical, social and historical context‐descriptions 3,27 . Since much standardized wording was used, we coded non‐standard texts with special attention.…”
Section: Discussionmentioning
confidence: 99%
“…The RTE select cases that (1) “are relevant for the further development of (ethical) norms or for the societal debate,” 26 that (2) provide insights into the “spectrum of cases reviewed and to contribute to the understanding of complex or controversial cases among physicians and the general public,” plus (3) some cases that are “considered common.” 27 After excluding dementia cases in which the main cause of suffering was not dementia, 111 cases were left to analyze.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Struggling with the age-related deterioration, he feels more and more disconnected from world around him, alternately unable or unwilling to reconcile himself with his estranged and resisting body. (based on the documentary Full Stop, 2020 1 ) Although most older adults succeed in finding meaning in life, even in deep old age (van Campen, 2020;van Campen & Verbeek-Oudijk, 2017), there is a minority of older adults who feel that life no longer makes sense (van Wijngaarden et al, 2015) As reflected in Michael's case, those people may suffer from the consequences of old age, explicated in feelings of loneliness, social isolation and disconnectedness, and fears for (further) decline and dependency. Consequently, some older adults may develop a wish to die (McCue & Balasubramaniam, 2017;Richards, 2017) + (van Wijngaarden et al, 2016;Hartog et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…4 A recent qualitative study from the Netherlands reported that, among 53 patients who underwent MAiD for "multiple geriatric syndromes," a combination of medical, social and existential issues was often associated with unbearable suffering leading to the MAiD request in the absence of a life-threatening condition. 5 When considering MAiD for frail individuals, it is essential that clinicians address this complex constellation of contributing factors, some of which may be modifiable. For example, frailty related to social isolation, depression and food insecurity may need to be addressed differently than frailty from poorly controlled diabetes, congestive heart failure and recurrent falls.Assessments for frail individuals who request MAiD are challenging given ambiguities in the interpretation of whether frailty is irreversible and incurable, and whether it causes intolerable suffering.…”
mentioning
confidence: 99%